A study on patient satisfaction in out patient department of secondary care hospital of Bhopal - Joshi, Sheloj; Joshi, Mahesh Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Patient satisfaction is as important as other clinical health measures and is a primary means of measuring the effectiveness of health care delivery. Patient-centered outcomes have taken central stage as the primary means of measuring the effectiveness of health care delivery. To evaluate the level of patient satisfaction with OPD services in terms of describing the experience of patients about medicine OPD services and accessibility to services among the patients who attended the medicine OPD of Jaiprakash hospital. Methods: As a cross -sectional descriptive study, we have taken patients who were registered in Medicine outpatient department of Jaiprakash Hospital of Bhopal over a period of two months. The research instrument for a data collection was a structured questionnaire for assessing the patient satisfaction. The experience and accessibility were categorized into good and poor while satisfaction into high and low using best criteria. Statistical analysis: Convenience sampling done for selection of patients registered in Medicine OPD. The data was analysed on statistical software SPSS VS.20. Results: The patients had the highest level of experience from medicine department OPD about helpfulness of nurses, about light and ventilation inside the OPD and about the good communication from the pharmacist. The poor experience was from the number of doctors in OPD and about the diagnostic place. As far as accessibility is concerned, 66% of patients had good accessibility towards medicine OPD while remaining 34% had poor accessibility towards Medicine OPD. Conclusions: Maximum number of respondents had very good experience while just small number of respondents had poor experience and majority of the patients had good accessibility regarding waiting time, service process and working hours.